2022
DOI: 10.3390/molecules27103194
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory Markers: Key Indicators in the Pathology of Neurodegenerative Diseases

Abstract: Neuroinflammation, a protective response of the central nervous system (CNS), is associated with the pathogenesis of neurodegenerative diseases. The CNS is composed of neurons and glial cells consisting of microglia, oligodendrocytes, and astrocytes. Entry of any foreign pathogen activates the glial cells (astrocytes and microglia) and overactivation of these cells triggers the release of various neuroinflammatory markers (NMs), such as the tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(74 citation statements)
references
References 244 publications
(298 reference statements)
1
73
0
Order By: Relevance
“…SIRT1 is a class III histone deacetylase that regulates various cellular functions, including oxidative stress, inflammation, energy metabolism, DNA damage repair, and cell death [ 63 , 64 ]. Increasing evidence suggests that neuroinflammation is closely associated with the pathogenesis of several neuronal diseases [ 65 , 66 ]. Extensive studies have demonstrated that SIRT1 has a neuroprotective effect on neuroinflammation-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is a class III histone deacetylase that regulates various cellular functions, including oxidative stress, inflammation, energy metabolism, DNA damage repair, and cell death [ 63 , 64 ]. Increasing evidence suggests that neuroinflammation is closely associated with the pathogenesis of several neuronal diseases [ 65 , 66 ]. Extensive studies have demonstrated that SIRT1 has a neuroprotective effect on neuroinflammation-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth mentioning that many challenging disorders are associated with a variety of objective proteins [ 32 , 33 , 34 ]. Furthermore, due to certain medicines having “poly-pharmacological” characteristics, unanticipated drug functionalities resulting from off-targets that are uncontrolled and unavoidable can lead to unpleasant side effects [ 7 , 35 , 36 , 37 , 38 , 39 ]. Sildenafil (Viagra), for example, is currently used to treat erectile dysfunction in men but was primarily designed for the treatment of angina [ 40 ].…”
Section: Anticancer Drug Target Predictionmentioning
confidence: 99%
“…Neuroinflammation is the complex innate immune response (sometimes adaptive) against internal or external agents, aiming to resist or resolve harmful threats to restore homeostasis [ 4 , 15 , 16 ]. Two glial cells, microglia and astrocytes, are cornerstones in this process as they restrain infection and eliminate pathogens, cell debris, and misfolded proteins.…”
Section: Glial Cell-mediated Neuroinflammationmentioning
confidence: 99%
“…The cornerstones of remyelination are glial cell-mediated neuroinflammation, the over-production of mitochondrial reactive oxygen species (ROS), and mitochondrial dysfunction. Importantly, these features occur in other neurodegenerative disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS) [ 4 ]. Another aspect common to neurodegenerative and/or neurological disorders, including MS, is the deficiency of the Nrf2 (nuclear factor erythroid 2-related factor 2) signaling pathway, a critical antioxidant transcription factor that prevents mitochondrial failure, oxidative stress, and neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%